ANALYSIS FINANCIAL DISTRESS USING ALTMAN Z-SCORE MODEL (GARMENT AND TEXTILE INDUSTRIAL SUBS SECTOR IN BEI 2018-2021) - Anugraheni, Vika Dahlia; Mardinawati, Mardinawati; Sadida, Afiat (Applied Accounting and Management Review (AAMAR), 2024)
Garments and textiles are sub-sectors that contribute to high GDP growth but, in 2020 and 2021 there has been a decline caused by a decrease in export demand. This will have an impact on the production process and profit that the industry is worried about will experience financial distress. The purpose of this study is to find out and analyze whether the Altman Z-Score model is influential and able to predict financial distribution in the garment and textile sub-sector industries registered with the BEI. The sampling techniques used in this study are purposive sampling and sampling techniques of 16 industries. This study used a quantitative approach with data collection techniques through documentation techniques sourced from secondary data in the form of industrial financial statements. The analysis method used is discriminant analysis using SPSS. The outcomes of this study show that working capital on total assets, retained earnings on total assets, pre-interest income and taxes on total assets, market value of equity on total liabilities, and sales on total assets are influential and able to predict financial distress in the garment and textile industries, with accuracy This model is 81.3%.  Keywords: Financial distress, bankruptcy predictions, Altman Z-Score..